2009
DOI: 10.1103/physrevb.80.155203
|View full text |Cite
|
Sign up to set email alerts
|

Magnetocrystalline anisotropies in (Ga,Mn)As: Systematic theoretical study and comparison with experiment

Abstract: We present a theoretical survey of magnetocrystalline anisotropies in ͑Ga,Mn͒As epilayers and compare the calculations to available experimental data. Our model is based on an envelope function description of the valence-band holes and a spin representation for their kinetic-exchange interaction with localized electrons on Mn 2+ ions, treated in the mean-field approximation. For epilayers with growth-induced lattice-matching strains we study in-plane to out-of-plane easy-axis reorientations as a function of Mn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
118
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(132 citation statements)
references
References 74 publications
(248 reference statements)
12
118
2
Order By: Relevance
“…Significant variations can be also found in the experimental magnetic anisotropy constants of (Ga,Mn)As (ref. 29). The disarray of the previously measured micromagnetic parameters reflects partly the lack of careful materials optimization but also the limitations of common magnetic characterization techniques when applied to the thin-film dilute-moment (Ga,Mn)As samples.…”
Section: Resultsmentioning
confidence: 99%
“…Significant variations can be also found in the experimental magnetic anisotropy constants of (Ga,Mn)As (ref. 29). The disarray of the previously measured micromagnetic parameters reflects partly the lack of careful materials optimization but also the limitations of common magnetic characterization techniques when applied to the thin-film dilute-moment (Ga,Mn)As samples.…”
Section: Resultsmentioning
confidence: 99%
“…This term can be evaluated theoretically using an effective mass Hamiltonian with the six-band k.p Luttinger-Kohn term, a strain tensor, and the p-d exchange interaction of the holes and the Mn spins in the molecular-field approximation 21,40 . The saturation magnetization was set to 6 kA.m −1 (T ≈ 95 K), which corresponds to a |B G | ≈4 meV spin splitting parameter 21 .…”
Section: B Derivation Of the Strain Wave Expressionmentioning
confidence: 99%
“…The saturation magnetization was set to 6 kA.m −1 (T ≈ 95 K), which corresponds to a |B G | ≈4 meV spin splitting parameter 21 . The usual biaxial strain terms ε zz,0 , ε xx,0 were set to zero, and a non-zero term idε xz introduced in the Bir-Pikus strain tensor, where d=-4.8 eV is the shear deformation potential 40 . In this way, B c and A 2xz were the only unknown parameters in the free energy density.…”
Section: B Derivation Of the Strain Wave Expressionmentioning
confidence: 99%
“…So far, however, to the best of our knowledge, there is no consensus in the literature concerning the origin of the in-plane uniaxial anisotropy. Although in some recent theoretical works the origin of the uniaxial in-plane anisotropy is attributed to a trigonal distortion caused by a uniaxial or shear strain within the film plane, 13,18,21 this type of distortion was not observed experimentally. Recently, Werpachowska and Dietl 22 suggested that the anisotropy mechanism in (Ga,Mn)As films originates from Dzyaloshinsky-Moriya interactions, without assuming any in-plane lattice distortion within their model.…”
mentioning
confidence: 99%